Sistem Pendukung Keputusan Pemilihan Varietas Unggul Jagung Hibrida Menggunakan Metode AHP-SMART - R Moh Andriawan Adikara; Muhammad Tanzil Furqon; Achmad Arwan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Corn proudction in Indonesia is still continue to rise. Although in 2016 Indonesian corn production is currently at 17 million tons, it is still behind the United States with 365 million tons in corn production. The amount of corn production will affect the level of exports and imports that directly affect the country's economy. Increased corn production can be done in various ways, one of which is the improvement of cultivation techniques with the use of superior varieties. According to available data from the Indonesian Ministry of Agriculture, there are 100 hybrid corn varieties, but of the many varieties of corn, there are still varieties that have not been able to increase the corn's production significantly. Selection of corn varieties becomes a problem because there are many criteria to consider. Solutions from the selection of corn varieties can be solved by decision support system method called AHP and SMART method. The AHP method is used to give weighting to the criteria used in the SMART method. The SMART method is used to rank superior corn varieties. Both methods are selected for being able to produce accurate and fast computing decisions. The result of the system is in the form of rank of corn varieties ranging from the best to the worst.System validation is done by using Spearman Rank correlation with = 0,99754 which means a relationship between result system and expert result is near perfect.